Habitat use, disturbance and collision risks for Bewick - Fijn, Ruben C; Krijgsveld, Karen L; Tijsen, Wim; Prinsen, Hein A M; Dirksen, Sjoerd (Wildfowl, 2012)
Each winter 30% of the Northwest European Bewick’s Swan Cygnus columbianus bewickii population feeds in Polder Wieringermeer, the Netherlands, on waste crops left after the harvest. The area has also become important for generating energy as a result of wind farm development. This study analyses pre- and post-construction data on Bewick’s Swan distribution, movements and foraging behaviour in the vicinity of a nine-turbine wind farm site, in order to determine the effects of wind turbines on wintering swans. The swans’ flight-lines between feeding areas and the roost were recorded visually and using radar over 10 evenings in good weather conditions. Food availability on different agricultural plots appeared to be an important factor explaining swan numbers and distribution in the area. In circumstances with even food availability early in the season, swans showed a preference for foraging in areas further away from the turbines, indicating some displacement caused by the turbines. Nevertheless, swans increasingly fed closer to the wind turbines during the course of the season in response to food availability. The likelihood that a single Bewick’s Swan passing through the wind farm will collide with a turbine (collision risk) at the nine-turbine site, determined from swan movements through the wind farm (number of swan flights per unit length per unit time) and from regular searches for carcasses, was estimated at 0–0.04% in winter 2006/2007. Avoidance behaviour was observed, with birds navigating around and between the lines of turbines. The observed disturbance of foraging birds early in the season, the acquired knowledge of avoidance responses, and the calculated collision rates in this study can be used for future assessments during planning and construction of new wind farms in wintering areas of Bewick’s Swans, especially in areas where important congregations of world or flyway populations occur.